If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1 + 3x = -7 + 6x + 6 Reorder the terms: -1 + 3x + 3x = -7 + 6x + 6 Combine like terms: 3x + 3x = 6x -1 + 6x = -7 + 6x + 6 Reorder the terms: -1 + 6x = -7 + 6 + 6x Combine like terms: -7 + 6 = -1 -1 + 6x = -1 + 6x Add '1' to each side of the equation. -1 + 1 + 6x = -1 + 1 + 6x Combine like terms: -1 + 1 = 0 0 + 6x = -1 + 1 + 6x 6x = -1 + 1 + 6x Combine like terms: -1 + 1 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5x-2+2x=-8+7x+6 | | -3=7(y=9/7) | | -3=7(y=9/7 | | -7x+-4x=-23 | | (-4.5)+4.9= | | 0.4y=520 | | 10x-1=9x+7 | | 3x^3+5x-10=0 | | 39x+33=540 | | 3(x-20)=102 | | n+(n-1)=35 | | (x+1)(1+1)=9x+6 | | ln(x^2-1)=ln(x-1)+1 | | y=-4*3+15 | | y=-4*2+15 | | 2x-4(x+3)=15 | | .3x+.5y=4 | | y=-2*6+19 | | y=-2*5+19 | | 23=8x-15+3x | | -5+(-7.1)= | | 2r-(5r-r)=13 | | 2cosx-5secx=3 | | 3x+7-2x=4x+13 | | 3x+11+10x=180 | | 15(x-5)=105 | | 2a-(-18)=18 | | 4(x-15)=168 | | 2x+10+3x+10=90 | | 49x^3-xy^2= | | (x-4)2+(y+5)2=25 | | X-2/5=-4 |